Analisis Performa Website Gemilang Travel Antarkota Menggunakan Automated Software Testing GtMatrix dan LoadFocus - Nugraha, Aditya Candra; Nuryasin, Ilyas (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
The performance analysis of the Gemilang Travel website is a study aimed at evaluating the performance of the Gemilang Travel website, which provides inter-city travel services and holiday packages. The main focus is on improving site access speed and stability. The method used includes performance and load testing with tools such as GTmetrix and LoadFocus. The test results are presented in tables with recommendations for improvement and enhancement. The results show good initial load times, but access speed still needs improvement. Additionally, load testing indicates that the system is capable of handling high loads with fast response times and without errors. Recommended improvements include optimizing images using Lazy Loading techniques and using placeholders to reduce layout shifts, which are expected to improve overall site performance.